Off-Label uses of Biologic Agents Approved for Psoriasis and Psoriatic Arthritis for Dermatological Conditions: Part I. Issue 1 (December 2016) - Elbendary, Amira; Kellen, Roselyn
Over the past decade or so, the treatment of patients with psoriasis has been revolutionized by the development of the biological agents, monoclonal antibodies that target specific aspects of the inflammatory cascades. The biologic agents approved by the Food and Drug Administration for psoriasis and psoriatic arthritis include adalimumab, etanercept, infliximab, ustekinumab, and secukinumab. The advantages of these agents are numerous: they are dosed less frequently than previously used systemic agents, they have a more favorable safety profile, and they have incredible efficacy even in patients resistant to standard treatment. There are abundant reports of off-label uses of these drugs for other dermatological conditions and inflammatory dermatoses. This review highlights the ability of the biologic agents to treat a wide spectrum of dermatologic diseases.